PENERAPAN STRATEGI EVERYONE IS A TEACHER HERE UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN MATEMATIS DAN KEMANDIRIAN BELAJAR SISWA SMP - Amalia Nurina, Lia (2012)
The aims of this research are intended to examine the effect of active learning strategy with Everyone is a teacher here type, toward the increase and achievement of student's mathematical understanding ability and self regulated learning. The research utilized a quasi experimental design. The population in this research are students of grade eight from one junior high school in Bandung. As concern, the sample comprised of 34 students in Everyone Is a Teacher Here class (experiment group) and 34 students in conventional class (control group). The research problem are to improve mathematical understanding ability, to improve student's self regulated learning, and the relationship between mathematical understanding ability and student's self regulated learning. The quantitative analysis is used independent sample t-test, Mann-Whitney test, Pearson Correlation, and Kendall Tau, while qualitative analysis is used descriptive one. The result shows better increasing mathematical understanding ability by active learning strategy with Everyone Is a Teacher Here type than by conventional teaching, student's self regulated learning in Everyone Is a Teacher Here class better than conventional class, and there is positive relationship between students mathematical understanding and self regulated learning.